Pengaruh Pelatihan Dan Disiplin Kerja Terhadap Kinerja Pegawai Balai Perikanan Budidaya Air Payau (BPBAP) Takalar - Astuti Astuti; Chalid Imran Musa; Abdi Akbar Idris; Siti Hasbiah; Tenri S.P Dipoatmodjo (Jurnal Manajemen dan Ekonomi Kreatif, 2023)
His research is to determine the effect of training and work discipline on the performance of employees of the Balai Perikanan Budidaya Air Payau (BPBAP) Takalar. The sample in this study was all employees of the Takalar Brackish Water Aquaculture Fisheries Center (BPBAP), totaling 83 employees. The data used is primary data and secondary data. Data collection was carried out using questionnaires, interviews and documentation. The data analysis techniques used in this research consist of validity tests, reliability tests, classical assumption tests, autocorrelation tests, multiple linear regression analysis, hypothesis tests and R determinant tests. The results of the research after the data were processed with SPSS.13 show that there is a positive influence between the Training variable (X1) on Employee Performance (Y) and the positive influence of Work Discipline (X2) on Employee Performance (Y) which can be shown through the results of the hypothesis test (t test) where the calculated t result is greater than the t table. Based on this description, it can be concluded that training and work discipline have a positive and significant effect on the performance of the employees of the Balai Perikanan Budidaya Air Payau (BPBAP) Takalar.